Proposed Design of Work Environment Management to Improve Work Performance and Productivity as Continuous Improvement Using the 6S Method - Aditya Rizki Hidayahtullah; Melfa Yola; Muhammad Ihsan Hamdy; Misra Hartati; Nofirza Nofirza (Fakultas Teknik Universitas Tulang Bawang, 2026)
The Rumbio Jaya Iron Brick Small and Medium Industry Center (IKM) is one of the metal business units that faces problems in the management of work areas, especially related to the lack of regularity and high potential hazards due to piles of goods that are not clearly identified. This shows that the implementation of the 6S work culture has not been carried out optimally. This research aims to design a strategy for the implementation of the 6S method and prepare SOPs that are in accordance with the characteristics and needs of the local work environment. To find out the initial condition of the work area, an evaluation was carried out using the 6S assessment form which included 32 assessment indicators, ranging from 1 to 5 assessment scores. Score 1 = 18 aspects, score 2 = 16 aspects, score 3 = 18 aspects, scores 4 and 5 = 0. The total score was 52 out of 160 points maximum, with an average score per indicator of 1.625. These results show that the 6S principle is still carried out in a limited way. Therefore, improvements were given, among others, the preparation of SOPs for each aspect of the 6S, the redesign of workstations, the construction of storage racks and labeling systems, the installation of boundary lines, and the implementation of daily inspections to ensure the consistency of its implementation. Keywords: Productivity, SOP, Work Culture, 6S